Factores motivacionales que generan satisfacción laboral en docentes de la institución educativa Pascual de Andagoya del distrito de Buenaventura - Orobio Mosquera, Wilmar (Universidad Antonio Nariño, 2021)
The purpose of this research process has been to describe the motivational factors that generate job satisfaction in teachers of the Pascual de Andagoya Educational Institution in the Buenaventura district, 2020. For the development of the work, two variables have been taken into account, according to the two-factor theory of Frederick Herzberg (1959), which refer to motivational factors and job satisfaction. The methodological design of the study accounts for a type of non-experimental quantitative research, and a descriptive cross-sectional scope, applied to a sample of 17 people. Inclusion and exclusion criteria were used for an initial population of 32 teachers, distributed over the two academic days. To collect the data, an instrument with two Likert-scale questionnaires was used, one to measure the degree of job satisfaction and the other to identify motivational factors. Among the main findings, it was found that the most relevant intrinsic motivational factors were work itself, responsibility and personal growth. On the other hand, it was found that the extrinsic motivational factors that generate job satisfaction have to do with safety, working conditions and interpersonal relationships. Finally, the dimensions with the highest scores according to the results are presented, which account for the work itself, achievements and responsibility.